Environment and Health Impact of Solid Waste Management in Developing Countries: A Review - Mahajan, Rinnie (Current world environment, 2023)
The subject of Solid Waste Management has attained global attention over recent years. This issue is observed to be more prominent in developing countries than in developed countries due to inadequate funds and resources. Solid waste generation, segregation practices, storage facilities, collection frequencies and disposal methods are evidenced to be unsustainable in developing countries. Uncontrolled dumping and open burning are common scenarios in these countries. Open dumping and burning of waste pose serious environmental and health risks. They have led to severe forms of air, water and soil pollution. Municipal Solid Waste pollution increases the mortality as well as morbidity of diseases. Thus, the present study reviews the environmental consequences and subsequent health jeopardies due to improper and inefficient Solid Waste Management. The study focuses more on environmental sustainability of Solid Waste Management than economic and social sustainability. Hence, a paradigm shift towards green and clean Solid Waste Management is vital as it safeguards the ecosystem while preserving a green economy and social equity amongst present and future generations.